2020 8th International Winter Conference on Brain-Computer Interface (BCI) 2020
DOI: 10.1109/bci48061.2020.9061638
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Dynamics of Visual Imagery for Intuitive Brain-Computer Interface

Abstract: Visual imagery is an intuitive brain-computer interface paradigm, referring to the emergence of the visual scene. Despite its convenience, analysis of its intrinsic characteristics is limited. In this study, we demonstrate the effect of time interval and channel selection that affects the decoding performance of the multi-class visual imagery. We divided the epoch into time intervals of 0-1 s and 1-2 s and performed six-class classification in three different brain regions: whole brain, visual cortex, and pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This allowed us to infer what trends and directions are being used to implement intuitive BCI communication. With the aim of decoding intuitive speech, BCI is evolving in conjunction with analyses using various paradigms (Cooney et al, 2018;Lee et al, 2020b;.…”
Section: Data Set-c Backgroundmentioning
confidence: 99%
“…This allowed us to infer what trends and directions are being used to implement intuitive BCI communication. With the aim of decoding intuitive speech, BCI is evolving in conjunction with analyses using various paradigms (Cooney et al, 2018;Lee et al, 2020b;.…”
Section: Data Set-c Backgroundmentioning
confidence: 99%
“…Qureshi et al [9] reported 32.9% of the fiveclass imagined speech classification accuracy using hybrid connectivity features and an extreme learning machine. As for visual imagery, the state-of-the-art performance remains at lower levels-55.9% for binary decoding [10] and 25.9% for six-class classification [11]. Lee et al [1] reported 20.4% and 22.2% in thirteen-class classification of imagined speech and visual imagery, respectively.…”
Section: Introductionmentioning
confidence: 99%